2019
DOI: 10.1016/j.iref.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of real options in the takeover premia in mergers and acquisitions

Abstract: This paper applies a real option framework to suggest that the takeover premia in mergers and acquisitions can be influenced by (a) the pre-bid ownership of target and (b) the real option characteristics of both acquirer and target firms. Our findings show that pre-bid ownership reduces the takeover premia, which is consistent with the argument that pre-bid ownership reduces information asymmetry. However, we find that the takeover premia is higher when both the acquirer and target firms exhibit real option ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Several authors viewed dynamic capabilities in terms of real options; however, they did not link capabilities and real options with the reciprocal synergies in M&A deals (Kyläheiko et al 2002;Jahanshahi and Nawaser 2018). Recently, scholars employed real options valuation to obtain the expected value of synergies arising from M&A deals, but they did not consider synergies as consequences of the dynamic capabilities (Loukianova et al 2017;Barbopoulos et al 2019). In the current paper, the author integrates the influence of dynamic capabilities on reciprocal synergies in open innovation type M&A deals into real options valuation and reconciles what has previously been presumed to be independent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors viewed dynamic capabilities in terms of real options; however, they did not link capabilities and real options with the reciprocal synergies in M&A deals (Kyläheiko et al 2002;Jahanshahi and Nawaser 2018). Recently, scholars employed real options valuation to obtain the expected value of synergies arising from M&A deals, but they did not consider synergies as consequences of the dynamic capabilities (Loukianova et al 2017;Barbopoulos et al 2019). In the current paper, the author integrates the influence of dynamic capabilities on reciprocal synergies in open innovation type M&A deals into real options valuation and reconciles what has previously been presumed to be independent.…”
Section: Introductionmentioning
confidence: 99%
“…These corporate assets also include the successful outcomes of outlays in research and development (R&D), learning outcomes acquired via M&A deals (Trigeorgis and Tsekrekos 2018). Having applied a real options framework to explore the role of real option in the takeover premia in M&A deals, Barbopoulos et al (2019) found that "an acquire with real option capacity is willing to pay higher takeover premia for an option embedded in the target firm" (Barbopoulos et al 2019, p. 19). The multi-step binomial model option pricing model can be useful as a "road map" framework to determine the value of growth options embedded in the M&A deals.…”
Section: Introductionmentioning
confidence: 99%
“…Having explored the synergistic combination of an acquirer and a target, scholars unpacked novel synergy sources and typical synergy management pitfalls of mergers and acquisitions (M&A) (Fiorentino and Garzella 2015;Sakhartov and Reuer 2021;Feldman and Hernandez 2021), but they did not bind synergism with the real options theory. Several authors employed the real options valuation to measure the synergy effect of M&A deals (Yu and Xu 2011;Loukianova et al 2017;Barbopoulos et al 2019), but they did not specify the type, timing, and duration of synergies in merger and acquisition (M&A) processes.…”
Section: Introduction: the Aim Motivation And Contributionsmentioning
confidence: 99%